1980
DOI: 10.1021/ic50206a008
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of boron trihalide electron affinities: correlation with boron-nitrogen adduct strengths

Abstract: The adiabatic electron affinities of several boron trihalides have been measured from the determination of threshold kinetic energies for the reaction Cs + BX3 + C s ' + BX). A crossed-molecular-beam apparatus was used. The electron affinities are Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 0 publications
3
16
1
Order By: Relevance
“…The adiabatic electron affinity of CO 2 in the gas phase is Ϫ0.6 eV, 60,61 and that of BF 3 is also slightly negative. [62][63][64] No absorption with a photodetachment threshold suitably low for assignment to HCl Ϫ has been detected in the present experiments.…”
Section: Anion Identificationcontrasting
confidence: 50%
“…The adiabatic electron affinity of CO 2 in the gas phase is Ϫ0.6 eV, 60,61 and that of BF 3 is also slightly negative. [62][63][64] No absorption with a photodetachment threshold suitably low for assignment to HCl Ϫ has been detected in the present experiments.…”
Section: Anion Identificationcontrasting
confidence: 50%
“…While spectroscopic studies of the relative Lewis acidities of boron trihalide donor-acceptor adducts have been extensive [33,34], experimental thermodynamic data are sparse for BX 3 adducts [35][36][37] and nonexistent for CX 3 + analogues. Gas-phase calorimetric measurements of TMAÁBX 3 (TMA = trimethylamine) show that the interaction energy is 3.9 kcal mol À1 lower for BCl 3 than for BF 3 [37] and the heats of reaction for BX 3 (X = F, Cl, Br) with pyridine and nitromethane show that the bond strengths increase in the order BF 3 < BCl 3 < BBr 3 [35]. Photoelectron studies have shown that the donor-acceptor interaction is stronger in the TMAÁBCl 3 and TMAÁBBr 3 adducts than in the BF 3 adduct [36].…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase studies 62-64 of electron capture by BF 3 yielded thresholds for anion production somewhat higher than 10 eV, with F Ϫ the principal product and F 2 Ϫ and BF 2 Ϫ formed in much lower concentration. Studies of crossed beams of Cs and BF 3 by Rothe and co-workers 65,66 gave F Ϫ as the only product anion. These workers concluded that, with an uncertainty of 0.2 eV, the electron affinity of BF 3 is less than zero.…”
mentioning
confidence: 99%